Diphenylpyrimidinone–salicylideneamine – new ESIPT based AIEgens with applications in latent fingerprinting. Issue 47 (16th November 2016) - Singh, Prabhpreet; Singh, Harminder; Sharma, Rashmi; Bhargava, Gaurav; Kumar, Subodh
Abstract : Green fluorescent aggregates of diphenylpyrimidinone–salicylideneamine show AIE + ESIPT in 99% H2 O:CH3 CN for the visualization of fingerprints on aluminium, steel, glass, ceramic tile and metal coin surfaces. Abstract : Diphenylpyrimidinone–salicylideneamineDPPS-1 undergoes concentration dependent self-assembly to form aggregates with rods – mimicking a ' coral reef ' superstructure and a spherical morphology evident from dynamic light scattering (DLS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM).DPPS-1 andDPPS-2 exhibit weak excited state intramolecular proton transfer (ESIPT) based emission in CH3 CN and their binary mixtures with water, but in solutions containing >70% water fractionDPPS-1 andDPPS-2 molecules aggregate and ESIPT is facilitated to give a strong green ESIPT emission at 526 nm ( ϕ = 0.273, 0.068). The ESIPT process remains active in the solid state and solidDPPS-1 andDPPS-2 appear as fluorescent green under 365 nm light illumination. The AIE-active nature ofDPPS-1 andDPPS-2 finds applications in the visualization of latent fingerprints on aluminium, steel and glass surfaces. Even 24 h after the placement of the fingerprints, up to the second level of information viz. core, lake, ridge termination and dots, delta and bifurcation in the fingerprints could be identified.